Dead Sea Scrolls: Transmission of Traditions and Production of Texts - Metso, Sarianna (Studies on the Texts of the Desert of Judah Ser., 2010)
This volume considers the transmission of interpretive traditions and the details of scribal practices. The essays explore the variety of ways that texts are interpreted at Qumran and also re-evaluates sectarian categorizations of texts along with distinctive scribal practices.